Light pollution in ultraviolet and visible spectrum: effect on different visual perceptions. - Héctor Antonio Solano Lamphar; Miroslav Kocifaj (PLoS ONE, 2013)
In general terms, lighting research has been focused in the development of artificial light with the purpose of saving energy and having more durable lamps. However, the consequences that artificial night lighting could bring to the human being and living organisms have become an important issue recently. Light pollution represents a significant problem to both the environment and human health causing a disruption of biological rhythms related not only to the visible spectrum, but also to other parts of the electromagnetic spectrum. Since the lamps emit across a wide range of the electromagnetic spectrum, all photobiological species may be exposed to another type of light pollution. By comparing five different lamps, the present study attempts to evaluate UV radiative fluxes relative to what humans and two species of insects perceive as sky glow level. We have analyzed three atmospheric situations: clear sky, overcast sky and evolving precipitable water content. One important finding suggests that when a constant illuminance of urban spaces has to be guaranteed the sky glow from the low pressure sodium lamps has the most significant effect to the visual perception of the insects tested. But having the fixed number of luminaires the situation changes and the low pressure sodium lamp would be the best choice for all three species. The sky glow effects can be interpreted correctly only if the lamp types and the required amount of scotopic luxes at the ground are taken into account simultaneously. If these two factors are combined properly, then the ecological consequences of sky glow can be partly reduced. The results of this research may be equally useful for lighting engineers, architects, biologists and researchers who are studying the effects of sky glow on humans and biodiversity.